A day with Dad - Amerikaner, Susan; Disney Storybook Artists (New York Random House, 2020)
Elf brothers Ian and Barley try to cast a spell to spend a magical day with their dad
"Over 30 stickers!"--Cover
At head of title: Disney Pixar Onward
English Stories
Keywords: Elves -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy; Easy reading materials; Elves -- Fiction; Elves; Father-son relationship -- Fiction; Fathers and sons; Magic -- Fiction; Magic; Readers (Elementary); Fantasy fiction; Fantasy fiction; Fantasy fiction; Fiction; Juvenile works; Readers (Elementary); Readers (Publications); Readers (Publications)